Regionalisms and resistance: region and ideology in the twentieth-century Portuguese novel - Haysom, Peter (2022)
This thesis constitutes a re-interpretation of regional spaces, landscapes and geographical dynamics in the twentieth-century Portuguese novel, through an ideological lens. Adopting politicised and spatialised understandings of the region, of regionalism, of ideology and of resistance, the study encompasses narratives published at different moments in the previous century, focusing on different regions of continental Portugal, and articulating distinct ideological projects. Chapter I conducts a diachronic overview of regional inequalities, divisions and tensions in Portuguese politics from the late nineteenth century to the early twenty-first, followed by an outline of regionalism’s ideological significance in narrative fiction over the same period.